SAT0502 Comparison between Oral or Intra-Articular Corticoids in the Management of Acute Gout Flare in Patients with Chronic Renal Failure. (10th June 2014) - Guillen Astete, C.A.; Boteanu, A.; Zea, A.
Abstract : Background: Chronic renal failure is a condition that limits the use of non steroidal anti-inflammatory drugs (NSAIDs) or colchicine. Both therapies should be used cautiously or avoided, and in its place many clinicians use glucocorticoids. Although it is a therapy commonly used worldwide, there are no clinical assays sustaining the superiority of intra articular glucocorticoids over oral administration. The aim of present study is to compare benefits of both therapies in terms of symptoms control. Objectives: The aim of present study is to compare benefits of both therapies in terms of symptoms control. Methods: Clinical charts of patients with chronic renal failure with a single joint flare of gout were reviewed. Only patients treated with glucorticoids (oral or intra articular) and who did not receive NSAIDs nor colchicine was included. Epidemiologic variables were analyzed and the effectiveness of both therapies (oral or intra articular glucocorticoids) was compared in terms of symptoms relief and time until resolution. All the data were obtained directly from the informatic archives and clinical charts of each patient. Resultd were grouped acoording to the way of glucocorticoid administration. Results: From 101 gout treatments selected, 69 (68.3%) were enough documented for the purposes of the study. Forty five patients (44.5%) were treated with joint injection of 20 to 40mg of triamcinolone (group I) and the rest received oral prednisone at a rate of 0.1-0.2 mg/kg/d (group II) or 0.2-0.3 mg/kg/d (group III). The proportion of patients treated also with opioids or who received a first intravenous corticoid dose was similar among the three groups treated orally with glucocorticoids. Therapeutic success was reached at day 15 in 75.5%, 62.5%, 75.0% and 75.0% of patients from groups I, II and III, respectively (p>0.05). No differences into the rate of local or systemic infections, hypertensive crisis or hyperglycemic status were detected among the three groups. The survival curve (symptoms relief) did not show differences accelerating or slowing the response variable according to any group of treatment (Coeff -0.1805 E.E. 0.1048 HR 0.8348 p 0.08). Conclusions: Our data do not support any superiority of the use of these different ways of glucocorticoids administration in a single joint gout flare in patients with chronic renal failure. In terms of relief of symptoms and security profile both strategies are similar. We conclude that both therapies could be used indistincly however larger studies should be performed in order to make posible important stratifications such as time of glucocorticoids administration, cumulative dosis, other therapies administered simultaneously or the joint affected. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3943